HAPPINESS AT WORK AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN KRAKATAU STEEL - Agustina, Granit; Permanar, Tatiek Ekawati; Nurhayati, Sri Endah; Ahman, Eeng; Febrian, Feby (Dinasti Publisher, 2020)
Every company must be able to invite its employees to provide a model of employee happiness at work and appropriate organizational citizenship behavior in accordance with the needs of the company which can make a person's organizational citizenship behavior better. This study aims to determine the model of employee happiness at work and organizational citizenship behavior of an employee in a company. This research is a descriptive and verification research using simple linear regression analysis, where the respondent population is all employees of 30 people with a sample size of 30 people using SPSS 24 software. The method used in this research is saturated sampling technique using the entire population as a sample. Collecting data using a direct survey method using a questionnaire. The results of respondents' responses that have been distributed and from the test results then employee happiness at work have a positive and significant effect on organizational citizenship behavior. To improve the organizational citizenship behavior of employees, the authors suggest that there be further research by other researchers on the issues of factors that influence organizational citizenship behavior besides happiness such as empathy at work, organizational conditions and the role of organizational management, supervisory ability and the quality of work itself.